Large carnivores as potential predators of sun bears, including probable predation on a sun bear cub by a leopard in Myanmar - Naing, H; Htun, S; Kamler, J; Burnham, D; Macdonald, D (International Association for Bear Research and Management, 2020)
Sun bears (Helarctos malayanus) have a wide distribution in Southeast Asia, but little is known about their natural predators. During a camera-trap survey in 2018 in Htamanthi Wildlife Sanctuary, Myanmar, we photographed a male leopard (Panthera pardus) carrying a sun bear cub by the throat. This is the first reported case of probable predation on sun bears by leopards, and only their second confirmed predator. A literature review showed that consumption of sun bears and Asiatic black bears (Ursus thibetanus) by tigers (Panthera tigris) was widespread in Southeast Asia, whereas consumption of both bear species by leopards and dholes (Cuon alpinus) was less common. Outside of Southeast Asia, tigers and leopards, but not dholes, were shown to kill or consume other bear species. Future research should examine interspecific relationships between sun bears and large felids to better understand what, if any, impacts large felids have on sun bear ecology.